2001
DOI: 10.1007/s101510170009
|View full text |Cite
|
Sign up to set email alerts
|

Perineal endometriosis in episiotomy scar with anal sphincter involvement

Abstract: Perineal endometriosis, especially with anal sphincter invasion, is a rare occurrence. We present a patient with perineal endometriosis in an episiotomy scar with anal sphincter involvement. The endometriotic mass was completely excised under general anesthesia with portions of the episiotomy scar and external anal sphincter. The procedure was followed by overlapping sphincter reconstruction. The excised mass was sent for microscopic examination, which confirmed endometriosis. The postoperative course was with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Kanellos et al [12] reported that good anal sphincter function was confirmed by anal manometry in the case they presented. In the two cases presented in this report, anal manometry was performed pre-and postoperatively, showing only a small drop in anal pressures 1 year after operation.…”
Section: Discussionmentioning
confidence: 96%
“…Kanellos et al [12] reported that good anal sphincter function was confirmed by anal manometry in the case they presented. In the two cases presented in this report, anal manometry was performed pre-and postoperatively, showing only a small drop in anal pressures 1 year after operation.…”
Section: Discussionmentioning
confidence: 96%
“…He observed recurrence in patient treated with only surgery; however, none of the patients treated with surgical and medical combination had recurrence of disease. Kanellos et al [13] presented a patient with perineal endometriosis in an episiotomy scar with anal sphincter involvement. The procedure was followed by overlapping sphincter reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It enables the surgeon to plan an operative strategy and explain to the patient the possible complications of sphincteroplasty. 28 The goal is to excise the endometriosis completely, which may compromise the anal sphincter. This may necessitate primary sphincteroplasty to lessen the risk of fecal incontinence.…”
Section: Perineal Endometriosismentioning
confidence: 99%